The Factors Affecting Students’ Inability in Vocabulary Mastery - Maria Rosa Lina Sitinjak; Elvy Dwi Aprillia Br Bangun; Elvira Rosyida M.R.; Yenita Br Sembiring (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study explores the internal and external factors affecting students’ inability to master English vocabulary, focusing on eighth-grade students at SMP Nasrani 5 Medan. Using a descriptive qualitative approach, data were gathered through questionnaires, interviews, and classroom observations involving 12 students. The findings revealed that internal factors such as low motivation, lack of interest, fear of making mistakes, and poor study habits significantly hinder vocabulary retention and usage. Meanwhile, external factors including monotonous teaching methods, limited access to learning resources, and an unsupportive environment further exacerbate the issue. Most students reported a lack of confidence, minimal English exposure outside class, and inadequate parental or institutional support. The study concludes that vocabulary mastery is impeded by a combination of psychological, pedagogical, and environmental factors. It recommends the adoption of interactive teaching strategies, provision of adequate learning resources, and increased involvement from teachers and parents to improve vocabulary acquisition. These findings are expected to contribute to the improvement of English language teaching practices at the junior high school level.